Geographic Information System for Tourism in Dairi Regency with Circular Method - Hutahaean, Harvei Desmon; Ali Akbar Lubis; Rosma Siregar (Cattleya Darmaya Fortuna, 2025)
There are plenty of tours in Indonesia, however not all tourist destinations are adequately run by the local government, and associated parties are less equipped to advertise travel online. As a result, many visitors avoid tourist destinations with poorly maintained information. The solution to the issues facing the tourism industry is the Geographic Information System. Geographic information systems are created using a circular approach, which can subsequently assist potential travelers who wish to visit a location by looking for tourist attractions to visit. Travelers can view the locations they wish to visit along with maps, and related parties will also benefit from foreign exchange input from tourists. Therefore, it is anticipated that this research will result in a geographic information system that aids in recommending various tourist places that are appropriate to visit.